Welcome to Silver Street Farm - Davies, Nicola, 1958- (Silver Street Farm, 2012)
"What are three city friends to do when a couple of newly adopted baby poodles turn out to be sheep and some eggs thought to be rotten hatch into ducklings? For Gemma, Meera, and Karl, the answer's easy--turn the abandoned train station into a city farm! Throw in a friendly policeman, a chicken-herding dog, and a pair of runaway goats, and you've got yourself the start of Silver Street Farm--the little farm in the big city. Welcome to Silver Street Farm!"--Jkt. flap.